A6.8 Tissue chitchat: wired communication between cells. (13th February 2015) - Byrne, RA; von Dalwigk, K; Olmos Calvo, I; Kartnig, F; Rothbauer, M; Charwat, V; Karonitsch, T; Ertl, P; Steiner, G; Schöfer, C; Holinka, J; Smolen, JS; et al.
Abstract : Background: The synovium is primarily built by fibroblast-like synoviocytes (FLS) that are connected to one another via cellular processes, thus forming a continuous network of cells. Its multicellularity requires precise coordination between cells to bring forth specialised tissue functions critical to joint homeostasis. Cell-to-cell transfer of cytoplasmic cargo may provide a means for intercellular communication, thereby facilitating the concerted behaviour of FLS. Using a 3D in-vitro model of the synovium, we analysed FLS capacity for exchange of cytoplasmic content. Methods: Human FLS were prepared from synovial tissues obtained as discarded specimens following joint arthroplasty. Cells were cultured in spherical matrigel micromasses with an average size of 2 mm Ø. For confocal live cell imaging and transmission electron microscopy, FLS were loaded with fluorescent non-degradable microspheres and labelled with fluorescent membrane dyes. Analysis of the resulting 4D movies was done with Imaris ® software. Results: To examine intercellular cytoplasmatic transfer, we labelled 50% of FLS with red cell tracker dye and loaded the other 50% with green microspheres. In a time series (8 days), we found that microspheres do indeed appear in red labelled cells. First evidence was found on Day 1 and over the course of the following days microspheres accumulated in red labelled cells with a transfer rate of 10% of newly affected cells/day. A similar experiment in 2D demonstrated microsphere movement within interconnecting membrane nanotubes. Transfer rates for microspheres into red cells were identical. Transmission Electron Microscopy (TEM) identified extracellular vesicles (exosomes) in discrete regions of intimate cell-to-cell contact but also open interconnecting tubes, suggesting distinct modes for transfer. Conclusions: These studies reveal transfer of cytoplasmic cargo between FLS and may provide insight into how the synovial tissue operates. Further studies will demonstrate the significance of directed cargo exchange for cellular cooperation and the function of the normal as well as the diseased synovium.